Chocolate : Riches from the Rainforest - Burleigh, Robert (New York : Harry N. Abrams, 2002)
Traces the history of chocolate from a drink of the Olmec and Maya and later in Europe to its popularity around the world today.
Keywords: Cookery (Chocolate) -- Juvenile literature; Chocolate -- Juvenile literature; Chocolate